FATAMORGANA ISLAMSKE UMJETNOSTI: RAZMIŠLJANJA O PROUČAVANJU JEDNE OPSEŽNE OBLASTI (III .) - Blair, Sheila S.; Bloom, Jonathan M.; Abadžić-Hodžić, Aida (Novi Muallim, 2009)
(„The mirage of Islamic art: reections on the study of an unwieldy eld“, Art Bulletin, 00043079, Vol. 85, „College Art Association of America“, 2003.) Prijevod s engleskog: Aida Abadžić-Hodžić